2022
DOI: 10.3390/cells11111850
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology in Glioblastoma Multiforme Treatment

Abstract: Glioblastoma (GBM, grade IV astrocytoma), the most frequently occurring primary brain tumor, presents unique challenges to therapy due to its location, aggressive biological behavior, and diffuse infiltrative growth, thus contributing to having disproportionately high morbidity and mortality [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Consequently, the role of CXCL5 in GBM remains only partially understood, and the associated target molecules await further elucidation. Additionally, given the complexity of tumor mechanisms, our choice of models and initial exploration of mechanisms may not have fully addressed the multifaceted nature of GBM [ 25 27 ]. Therefore, future research endeavors should prioritize mechanistic experiments to unveil the intricacies of immune infiltration patterns and elucidate CXCL5's role in drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the role of CXCL5 in GBM remains only partially understood, and the associated target molecules await further elucidation. Additionally, given the complexity of tumor mechanisms, our choice of models and initial exploration of mechanisms may not have fully addressed the multifaceted nature of GBM [ 25 27 ]. Therefore, future research endeavors should prioritize mechanistic experiments to unveil the intricacies of immune infiltration patterns and elucidate CXCL5's role in drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the implementation of aggressive multidisciplinary interventions, GBM continues to manifest dismal prognostic outcomes. Typically, patients encounter a median progression-free survival (PFS) of merely 6-7 months, coupled with an overall survival (OS) spanning 14-16 months from the point of initial diagnosis [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] High proliferation and invasion activity as well as the heterogeneous appearance of the tumor are responsible for its malignancy. [ 2 ] The interaction with its tumor microenvironment (TME) is of particular importance for tumor proliferation, e.g., it was shown that tumor cells take advantage of the interactions with other cell types in the brain. [ 3,4 ] GBM´s TME is composed of microglia, neurons, astrocytes, and vascular cells.…”
Section: Introductionmentioning
confidence: 99%